2001
DOI: 10.1017/s1357729800055739
|View full text |Cite
|
Sign up to set email alerts
|

Selection for ultrafine Merino sheep in New Zealand: heritability, phenotypic and genetic correlations of live weight, fleece weight and wool characteristics in yearlings

Abstract: Merino yearling records from 1988 to 1992 birth years in ultrafine wool selection and random control flocks at Tara Hills High Country Station, New Zealand were analysed for live weight, fleece weight and wool characteristics. Estimates of heritability, genetic and phenotypic correlations among traits using REML methods are presented. Heritabilities (h 2 ) of birth, weaning, autumn, spring and summer live weights and greasy and clean fleece weights were estimated as being 0·35were found to be high among the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 21 publications
(39 reference statements)
5
14
3
1
Order By: Relevance
“…Reported estimates direct heritability for different sheep breeds range from 0.00 to 0.38 for lamb birth weight, 0.025 to 0.49, for weaning weight (Babar et al, 2003;Bahreini et al, 2007;Duru and Koyuncu, 2005;Hanford et al, 2006;Ligda et al, 2000;Maria et al, 1993;Carrillo and Segura, 1993;Hanford et al, 2003;Nakagawa et al, 2005;Noter and Hough, 1997;Ozcan et al, 2005;Reale et al, 1999;Sawalha et al, 2005;Szwaczkowski et al, 2006;Tosh and Kemp, 1994;Wuliji et al, 2001;Wyk et al, 2003) and 0.12 to 0.25 for yearling weights (Reale et al, 1999;Ozcan et al, 2005), and 0.11 to 0.33 for average daily gain (Carrillo and Segura, 1993;Maria et al, 1993;Noter and Hough, 1997;Ozcan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reported estimates direct heritability for different sheep breeds range from 0.00 to 0.38 for lamb birth weight, 0.025 to 0.49, for weaning weight (Babar et al, 2003;Bahreini et al, 2007;Duru and Koyuncu, 2005;Hanford et al, 2006;Ligda et al, 2000;Maria et al, 1993;Carrillo and Segura, 1993;Hanford et al, 2003;Nakagawa et al, 2005;Noter and Hough, 1997;Ozcan et al, 2005;Reale et al, 1999;Sawalha et al, 2005;Szwaczkowski et al, 2006;Tosh and Kemp, 1994;Wuliji et al, 2001;Wyk et al, 2003) and 0.12 to 0.25 for yearling weights (Reale et al, 1999;Ozcan et al, 2005), and 0.11 to 0.33 for average daily gain (Carrillo and Segura, 1993;Maria et al, 1993;Noter and Hough, 1997;Ozcan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fogarty (1995) has presented an exclusive review of genetic parameters in sheep including some of wool traits, and our estimates are generally consistent with these published heritability estimates for crossbreed sheep. Heritability estimates for GF, CF, FD and bulk in Romney are comparable with the estimates in New Zealand Merinos (Wuliji et al, 2001), while they largely differed for other wool traits such as SL and wool colour. The heritability estimates in this trial appeared to be lower than estimates in some North American dual use sheep breeds (Okut et al, 1999;Bromley et al, 2000;Hanford et al, 2002Hanford et al, , 2003.…”
Section: Discussionmentioning
confidence: 53%
“…The genetic and phenotypic correlation was high among SW, GF and CF, and was moderate to high for GF and CF with FD, SL and SS, while there was a negative correlation between Y and Y-Z colour traits. Phenotypic and genetic correlations are within expectation and recently published literature (Fogarty, 1995;Wuliji et al, 2001). Breeding objectives in earlier selection experiments placed a strong emphasis on fleece weight, but wool quality traits are becoming increasingly important to meat-wool dual use sheep breeding.…”
Section: Discussionmentioning
confidence: 55%
“…The mean heritability found in the present study was around 0.65 times that reported by Wuliji et al . () and by Pollott & Greeff (), with means of 0.49 ± 0.12 and 0.47 ± 0.018, respectively, for live weight of Merino sheep when fitting animal models with and without maternal effects. However, the heritability estimate of BW obtained in the present study was very similar to those reported by Safari et al .…”
Section: Resultsmentioning
confidence: 94%